Coastal Literacy Camp: Strengthening Cultural Literacy and Local Wisdom among Coastal Youth in Karimunjawa - Ainun Yudhistira; Hakiman; Abdulloh Hadziq; Raha Bistara (LP2M of Institute for Research and Community Services - UIN Walisongo, 2026)
The development of Karimunjawa as a national and international tourism destination presents both opportunities and challenges for the sustainability of coastal communities’ culture and local wisdom. The increasing flow of tourism and the rapid advancement of digital technology require coastal youth not only to adapt to social transformation but also to develop awareness of preserving their local cultural identity from erosion in the face of changing times. This community engagement program aims to strengthen digital-based cultural literacy among coastal youth in Karimunjawa as a strategy to preserve, develop, and promote cultural values and local wisdom within the local community. The program employed an Asset-Based Community Development (ABCD) approach, emphasizing the identification and optimization of cultural assets owned by coastal communities. The activities involved 30 participants, comprising representatives from youth groups, traditional leaders, educational institutions, and local community members. The program was implemented through several stages, including cultural asset mapping, digital literacy training, and strengthening community networks. Data were collected through observation, interviews, questionnaires, and Focus Group Discussions (FGDs), and were analyzed using a descriptive qualitative and quantitative approach. The findings reveal that the Literacy Camp significantly strengthened coastal youths’ competencies, increasing cultural awareness from 60.0% to 87.4% (27.4%), digital literacy capacity from 58.0% to 89.2% (31.2%), and community participation from 62.0% to 86.6% (24.6%). These improvements enhanced their ability to recognize, preserve, and develop Karimunjawa’s local cultural assets. Young people are not merely cultural inheritors but also key actors in documenting and promoting marine tourism, traditions, and local wisdom through digital platforms. The Literacy Camp strengthens digital and cultural literacy among Karimunjawa youth, preserving local wisdom, empowering communities, supporting sustainable ecotourism, and requiring continuous collaboration for cultural sustainability and community welfare development.